Bottlenecks in carotenoid biosynthesis and accumulation in rice endosperm are influenced by the precursor–product balance. Issue 1 (7th April 2015) - Bai, Chao; Capell, Teresa; Berman, Judit; Medina, Vicente; Sandmann, Gerhard; Christou, Paul; Zhu, Changfu
Summary: The profile of secondary metabolites in plants reflects the balance of biosynthesis, degradation and storage, including the availability of precursors and products that affect the metabolic equilibrium. We investigated the impact of the precursor–product balance on the carotenoid pathway in the endosperm of intact rice plants because this tissue does not normally accumulate carotenoids, allowing us to control each component of the pathway. We generated transgenic plants expressing the maize phytoene synthase gene ( ZmPSY1 ) and the bacterial phytoene desaturase gene ( PaCRTI ), which are sufficient to produce β‐carotene in the presence of endogenous lycopene β‐cyclase. We combined this mini‐pathway with the Arabidopsis thaliana genes AtDXS (encoding 1‐deoxy‐D‐xylulose 5‐phosphate synthase, which supplies metabolic precursors) or AtOR (the ORANGE gene, which promotes the formation of a metabolic sink). Analysis of the resulting transgenic plants suggested that the supply of isoprenoid precursors from the MEP pathway is one of the key factors limiting carotenoid accumulation in the endosperm and that the overexpression of AtOR increased the accumulation of carotenoids in part by up‐regulating a series of endogenous carotenogenic genes. The identification of metabolic bottlenecks in the pathway will help to refine strategies for the creation of engineered plants with specific carotenoid profiles.